Zn (II)‐Doped Cesium Copper Halide Nanocrystals with High Quantum Yield and Colloidal Stability for High‐Resolution X‑Ray Imaging. Issue 7 (19th January 2023) - Qu, Kang; Lu, Yangbin; Ran, Peng; Wang, Kun; Zhang, Nan; Xia, Kaiyu; Zhang, Hongyan; Pi, Xiaodong; Hu, Hanlin; Yang, Yang (Michael); He, Qingquan; Yin, Jun; et al.
Abstract: Scintillators are essential for high‐energy radiation detection in a variety of potential applications. However, due to complex fabrication processes and nanocrystal homogeneity, conventional scintillators are challenging to meet the need for cost‐effective, environmentally friendly, and flexible X‐ray detection. Here, monodisperse nanocrystals (NCs) with small grain size and colloidal stability are obtained by adjusting the doping concentration of Zn 2+ ions and controlling the morphology uniformity of Cs3 Cu2 I5 NCs. The photoluminescence quantum yield (PLQY) for the optimal doping concentration is as high as 92.8%, which is a 28.5% improvement compared to nondoped NCs. Density functional theory calculations reveal that the Zn 2+ dopant inclines to occupy Cu sites and the I‐rich condition suppresses the formation of I vacancy, enriching the excited electron density at the band‐edge to enhance the self‐trapped exciton emission. Moreover, high luminescence performance and flexible X‐ray scintillator films are prepared using Zn 2+ ‐doped Cs3 Cu2 I5 NCs, with a spatial resolution of up to 15.7 lp mm –1 . This work provides an effective strategy for the development of environmentally friendly, low‐cost, and efficient blue‐emitting 0D all‐inorganic metal halides, as well as shows their great potential for high‐performance flexible lead‐free and low‐toxicity X‐ray detector applications. Abstract : The growth process of Cs3 Cu2 I5 nanocrystals is regulated by the doping of zinc ions, and monodisperse nanocrystals with photoluminescence quantum yields up to 92.8% are obtained. The resulting nanocrystals are embedded into ethylene vinyl acetate to obtain flexible and environmentally friendly scintillator films with a spatial resolution up to 15.7 lp mm –1 .